Strategic Market Management and Digital Literacy in Preventing Business Failures Among Indonesian Migrant Workers - Lies Trisna Susanti; Hartanti Nugrahaningsih (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: This study investigates the role of strategic market management and digital marketing literacy in preventing the failure of micro-enterprises managed by former Indonesian Migrant Workers (PMIs) in Korea. Despite contributing significantly to Indonesia’s economy, Micro, Small, and Medium Enterprises (MSMEs) face high failure rates, particularly among PMIs who struggle with market knowledge, managerial skills, and adapting to digital tools.Purpose: The research emphasizes the importance of market research, business strategy, and digital literacy in overcoming the challenges faced by PMIs in managing their businesses and preventing failure.Design/methodology/approach: A quantitative approach was employed, with primary data collected in August 2025 from 104 PMIs managing micro-enterprises using structured questionnaires. The analysis was performed using SmartPLS 4.0 to assess the relationships between market research, business strategy, and digital literacy.Findings/Result: The findings revealed significant relationships between market research, business strategy, and digital literacy. All factors were found to play a crucial role in preventing business failures. The study found that enhancing digital marketing literacy and integrating market research into business strategies significantly boosts the sustainability of these businesses.Conclusion: The study concludes that improving digital marketing literacy and incorporating market research into business strategies are essential for enhancing the sustainability and success of micro-enterprises managed by PMIs. It also highlights the need for targeted programs to improve business management skills and digital capabilities.Originality/value (State of the art): This study provides valuable insights into supporting PMIs by developing targeted programs that improve business management skills and digital capabilities. It also offers recommendations for policies that foster resilience in micro-enterprises, ensuring their long-term growth and success in a competitive market environment. Keywords:   micro small and medium enterprises (MSMEs), business failure prevention, SMART PLS analysis, managerial skill, business sustainability